EGF receptor attenuates dpp signaling and helps to distinguish the wing and leg cell fates in Drosophila. - Kubota, K.; Goto, S.; Eto, K.; Hayashi, S. (Development, 2000)
Wing and leg precursors of Drosophila are recruited from a common pool of ectodermal cells expressing the homeobox gene Dll. Induction by Dpp promotes this cell fate decision toward the wing and proximal leg. We report here that the receptor tyrosine kinase EGFR antagonizes the wing-promoting function of Dpp and allows recruitment of leg precursor cells from uncommitted ectodermal cells. By monitoring the spatial distribution of cells responding to Dpp and EGFR, we show that nuclear transduction of the two signals peaks at different position along the dorsoventral axis when the fates of wing and leg discs are specified and that the balance of the two signals assessed within the nucleus determines the number of cells recruited to the wing. Differential activation of the two signals and the cross talk between them critically affect this cell fate choice.